2008
DOI: 10.1111/j.1476-5829.2008.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteomic profiling of serum peptides in canine lymphoma and transitional cell carcinoma

Abstract: Differential expression of fucosylated glycoproteins has been correlated with malignancy and metastatic potential in various types of neoplasia. Utilizing glycoproteomics techniques, changes in fucosylated serum peptides associated with naturally occurring canine lymphoma and transitional cell carcinoma (TCC) have been evaluated. In both types of neoplasia, the majority of the fucosylated peptides that changed increased with the cancer. In one lymphoma case that was examined over the course of the disease, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Furthermore, the comparison of all fucosylated peptides detected in lymphoma and TCC, revealed only two common peptides for the two different forms of cancer. The results of the study indicated the power of glycoproteomics in discriminating between fucosylation of specific glycopeptides in two different types of cancer in dogs (Wilson et al, 2008). Modulation in the glycosylation of the APP HPT in serum from dogs with several diseases including anaemia, inflammation, lymphoma, and chronic progressive hepatitis has also been reported (Anderssen et al, 2001).…”
Section: Post-translational Modification Of Acute Phase Proteins Durimentioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, the comparison of all fucosylated peptides detected in lymphoma and TCC, revealed only two common peptides for the two different forms of cancer. The results of the study indicated the power of glycoproteomics in discriminating between fucosylation of specific glycopeptides in two different types of cancer in dogs (Wilson et al, 2008). Modulation in the glycosylation of the APP HPT in serum from dogs with several diseases including anaemia, inflammation, lymphoma, and chronic progressive hepatitis has also been reported (Anderssen et al, 2001).…”
Section: Post-translational Modification Of Acute Phase Proteins Durimentioning
confidence: 86%
“…In veterinary research, differential expression and increased abundance of fucosylated peptides have been reported for lymphoma and transitional cell carcinoma (TCC) in dogs (Wilson et al, 2008). The progression of canine lymphoma was monitored during the course of disease, and it was discovered that the same fucosylated peptides that increased during the pre-chemotherapy period were reduced post-chemotherapy treatments.…”
Section: Post-translational Modification Of Acute Phase Proteins Durimentioning
confidence: 99%
See 1 more Smart Citation
“…Glycoproteomic profile of serum peptides has been examined by a combination of lectin affinity selection, global internal standard technology, high-performance LC, and MALDI-TOF to investigate canine lymphoma and transitional cell carcinoma. 115 Two peptides were identified that allowed discrimination between these conditions.…”
Section: Proteomics and Posttranslational Modifications In Veterinarymentioning
confidence: 99%
“…86 Briefly, tryptic peptides were generated from serum samples of healthy and lymphoma-affected dogs. 87 Primary amines on peptides were then acylated with GIST isotope labelling reagents, and fucosylated peptides sorted by lectin binding affinity chromatography. After deglycosylation and fractionation, peptides were analysed and quantified with MALDI-TOF.…”
mentioning
confidence: 99%